Influence Climate Of Organizational And Work Ethic On The Performance Of Dinas Bina Marga Dan Bina Konstruksi South Sulawesi - Yohanis, Yohanis; Ranteta'dung, Rilfan Kasi; Hikmah, Hikmah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The aim of this research is to determine the influence of Organizational Climate and Work Ethic on the performance of State Civil Apparatus in Dinas Bina Marga Dan Bina Konstruksi Provinsi Sulawesi Selatan. This type of research is quantitative. The sampling technique in this study is purposive cluster random sampling, namely that each individual in the population in each field must have a known chance of being clarified as a choice in a study or more precisely as a sample in the study. The results of this study indicate that organizational climate and work ethic have a positive and significant effect on employee performance. The organizational climate variable has a T-value of 2.963 while the T value of the distribution table 0.05 (5%) is 2,000, so the t-value> t-table and the value of significant is 0.004> 0.05, meaning that the individual variable of physical evidence (organizational climate) X1 has a significant and positive effect on employee performance. For the Work Ethic variable, the t-value is 2.801 while the t-value of the distribution table 0.05 (5%) is 2,000, so the t-value> t-table and the value of significant is 0.007> 0.05, meaning that the individual variable of work ethic has a positive and significant effect on employee performance.